The Journal of Turkish Lıbrarianship in Her Fiftieth Year - Necmeddin Sefercioğlu (Türk Kütüphaneciliği)
Tlıis article examines an important part of publishing adventııre ofthe Türk Kütüphaneciler Derneği Bülteni (Bulletin of the Turkish Librarians’ Association) and its successor Türk Kütüphaneciliği (Turkish Librarianship), quarterly jour- nals of the Turkish Librarians’ Association, in their fiftieth year. In the article it is been given Information about their publishings and is beerı explained the dif- ficulties which was met face to face dur'ıng the year s of 1960-1992.The author had administered its publication for twentyfive years as technical secretary, editör and ‘ownerfor the association . On account ofthis, Information given in the article is important for histories of the Türk Kütüphaneciler Derneği Bülteni (Bulletin ofthe Turkish Librarians’ Association) and Türk Kütüphaneciliği (Turkish Librarianship)